2017
DOI: 10.1016/j.kint.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Podocytes regulate the glomerular basement membrane protein nephronectin by means of miR-378a-3p in glomerular diseases

Abstract: The pathophysiology of many proteinuric kidney diseases is poorly understood, and microRNAs (miRs) regulation of these diseases has been largely unexplored. Here, we tested whether miR-378a-3p is a novel regulator of glomerular diseases. MiR-378a-3p has two predicted targets relevant to glomerular function, the glomerular basement membrane matrix component, nephronectin (NPNT) and vascular endothelial growth factor VEGF-A. In zebrafish (Danio rerio), miR-378a-3p mimic injection or npnt knockdown by a morpholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 53 publications
5
91
0
Order By: Relevance
“…MiR-378a-3p was found in urines samples from patients with MGN, FSGS and MCD and upregulated in cultured human podocytes in response to TGF-β treatment. In a previous study we could confirm the importance of miR-378a-3p for glomerular function as it is a regulator of the glomerular matrix protein nephronectin [17]. Thus, our data confirm that urinary miRs seem to be markers for renal injury.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…MiR-378a-3p was found in urines samples from patients with MGN, FSGS and MCD and upregulated in cultured human podocytes in response to TGF-β treatment. In a previous study we could confirm the importance of miR-378a-3p for glomerular function as it is a regulator of the glomerular matrix protein nephronectin [17]. Thus, our data confirm that urinary miRs seem to be markers for renal injury.…”
Section: Discussionsupporting
confidence: 81%
“…For example, miR-378a-3p was specifically upregulated in cultured human podocytes. The importance of miR-378a-3p for glomerular filter function and ultrastructure was previously described by us [17].…”
Section: Mirs Regulated By Tgf-β In Cultured Renal Cellsmentioning
confidence: 82%
“…Cell adhesion assay analysis showed that the adhesion ability decreased significantly under the costimulation of high glucose combined with TGF‐β1, which suggested that podocyte dysfunction and injury occurred. At this moment, different concentrations of BBR (15, 30, 60 and 90 μmol/L) were added to the cultured cells, and the results showing that BBR could enhance the cell adhesion ability obviously seem to indicate that BBR could reverse podocyte dysfunction and injury after 48‐h stimulation.…”
Section: Discussionmentioning
confidence: 93%
“…The clinical relevance of miR-378a-3p was shown by the detection of upregulated miR-378a-3p in urine samples as well as glomeruli of kidney biopsies of patients with idiopathic membranous glomeruolonephritis and focal segmental glomerulosclerosis [24]. …”
Section: The Zebrafish Model To Study the Role Of Micrornas In Glomermentioning
confidence: 99%
“…The clinical relevance of miR-378a-3p was shown by the detection of upregulated miR-378a-3p in urine samples as well as glomeruli of kidney biopsies of patients with idiopathic membranous glomeruolonephritis and focal segmental glomerulosclerosis [24]. Due to the nature of miRs that often have multiple targets; we cannot rule out completely that the observed phenotypes in the zebrafish after miR-143-3p and miR-378a-3p over expression were due to knockdown of other targets than vcans and sdcs a.e.…”
mentioning
confidence: 99%